Kinetics of Viremia and NS1 Antigenemia Are Shaped by Immune Status and Virus Serotype in Adults with Dengue - Simmons, Cameron (2018)
BACKGROUND: Dengue is a major public health problem in tropical and subtropical countries. Exploring the relationships between virological features of infection with patient immune status and outcome may help to identify predictors of disease severity and enable rational therapeutic strategies. METHODS: Clinical features, antibody responses and virological markers were characterized in Vietnamese adults participating in a randomised controlled treatment trial of chloroquine. RESULTS: Of the 248 patients with laboratory-confirmed dengue and defined serological and clinical classifications 29 (11.7%) had primary DF, 150 (60.5%) had secondary DF, 4 (1.6%) had primary DHF and 65 (26.2%) had secondary DHF. DENV-1 was the commonest serotype (57.3%), then DENV-2 (20.6%), DENV-3 (15.7%) and DENV-4 (2.8%). DHF was associated with secondary infection (Odds ratio=3.13, 95% CI 1.04-12.75). DENV-1 infections resulted in significantly higher viremia levels than DENV-2 infections. Early viremia levels were higher in DENV-1 patients with DHF than with DF, even if the peak viremia level was often not observed because it occurred prior to enrolment. Peak viremias were significantly less often observed during secondary infections than primary for all disease severity grades (P=0.001). The clearance of DENV viremia and NS1 antigenemia occurs earlier and faster in patients with secondary dengue (P<0.0001). The maximum daily rate of viremia clearance was significantly higher in patients with secondary infections than primary (P<0.00001). CONCLUSIONS: Collectively, our findings suggest that the early magnitude of viremia is positively associated with disease severity. The clearance of DENV is associated with immune status, and there are serotype dependent differences in infection kinetics. These findings are relevant for the rational design of randomized controlled trials of therapeutic interventions, especially antivirals.